Mischmaterialschweißen von PC/ABS und PMMA beim Warmgasstumpfschweißen mit Runddüsen - Schöppner, Volker; Gevers, Karina; Albrecht, M.; Seefried, A.

Microwave Heating of Rubber Extrudates - Petzke, J.; Kleinschmidt, Dennis; Schöppner, Volker

Konturnah kühlen für wenig Geld - Moritzer, Elmar; Kartelmeyer, Stephan; Kringe, Roberg; Jaroschek, Christoph (Kunststoffe)

Wie war das damals? Oral history und Zeitzeug:innenbefragung - Diederich, Julia ((Über-)Leben im Nationalsozialismus)

Incremental permutation feature importance (iPFI): towards online explanations on data streams - Fumagalli, Fabian; Muschalik, Maximilian; Hüllermeier, Eyke; Hammer, Barbara (Machine Learning)
Abstract Explainable artificial intelligence has mainly focused on static learning scenarios so far. We are interested in dynamic scenarios where data is sampled progressively, and learning is done in an incremental rather than a batch mode. We seek efficient incremental algorithms for computing feature importance (FI). Permutation feature importance (PFI) is a well-established model-agnostic measure to obtain global FI based on feature marginalization of absent features. We propose an efficient, model-agnostic algorithm called iPFI to estimate this measure incrementally and under dynamic modeling conditions including concept drift. We prove theoretical guarantees on the approximation quality in terms of expectation and variance. To validate our theoretical findings and the efficacy of our approaches in incremental scenarios dealing with streaming data rather than traditional batch settings, we conduct multiple experimental studies on benchmark data with and without concept drift.
Keywords: Artificial Intelligence; Software

Single-shot spatial instability and electric control of polariton condensates at room temperature - Gao, Ying; Ma, Xuekai; Zhai, Xiaokun; Xing, Chunzi; Gao, Meini; Dai, Haitao; Wu, Hao; Liu, Tong; Ren, Yuan; Wang, Xiao; Pan, Anlian; Hu, Wei; et al. (Physical Review B)

Threshold photoelectron spectroscopy and dissociative photoionization of benzonitrile - Kamer, Jerry; Schleier, Domenik; Donker, Merel; Hemberger, Patrick; Bodi, Andras; Bouwman, Jordy (Physical Chemistry Chemical Physics)
The seven parallel dissociative ionization channels of benzonitrile yield highly stable fragment ions with commensurate abundance, underlining the potential role of the benzonitrile cation as hub species in the interstellar medium.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Role (in-)congruity and the Catch 22 for female executives: how stereotyping contributes to the gender pay gap at top executive level - Diederich, Sarah; Iseke, Anja; Pull, Kerstin; Schneider, Martin (The International Journal of Human Resource Management)
Keywords: Management of Technology and Innovation; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management; Industrial relations

Warum es ein Marketing für die Berufsbildung braucht – Zwei Fallstudien über die Verbesserung der Durchlässigkeit durch innovative Fortbildungen auf der DQR-Stufe 5 - Peitz, Nina-Madeleine; Müller-Wegner, Max; Ertl, Hubert
Mittels Fallstudien zweier Projekte des bundesweiten Programms InnoVET (Zukunft gestalten – Innovationen für eine exzellente berufliche Bildung) wird untersucht, wie innovative Aufstiegsfortbildungen auf der DQR-Stufe 5 zu einer durchlässigeren Berufsbildung im Verbund gestaltet und Ergebnisse transferiert werden. Zwecks nachhaltiger Implementation am Markt wird der Bedarf eines Marketings deutlich.

Segment-Less Continuous Speech Separation of Meetings: Training and Evaluation Criteria - von Neumann, Thilo; Kinoshita, Keisuke; Boeddeker, Christoph; Delcroix, Marc; Haeb-Umbach, Reinhold (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Continuous Speech Separation (CSS) has been proposed to address speech overlaps during the analysis of realistic meeting-like conversations by eliminating any overlaps before further processing. CSS separates a recording of arbitrarily many speakers into a small number of overlap-free output channels, where each output channel may contain speech of multiple speakers. This is often done by applying a conventional separation model trained with Utterance-level Permutation Invariant Training (uPIT), which exclusively maps a speaker to an output channel, in sliding window approach called stitching. Recently, we introduced an alternative training scheme called Graph-PIT that teaches the separation network to directly produce output streams in the required format without stitching. It can handle an arbitrary number of speakers as long as never more of them overlap at the same time than the separator has output channels. In this contribution, we further investigate the Graph-PIT training scheme. We show in extended experiments that models trained with Graph-PIT also work in challenging reverberant conditions. Models trained in this way are able to perform segment-less CSS, i.e., without stitching, and achieve comparable and often better separation quality than the conventional CSS with uPIT and stitching. We simplify the training schedule for Graph-PIT with the recently proposed Source Aggregated Signal-to-Distortion Ratio (SA-SDR) loss. It eliminates unfavorable properties of the previously used A-SDR loss and thus enables training with Graph-PIT from scratch. Graph-PIT training relaxes the constraints w.r.t. the allowed numbers of speakers and speaking patterns which allows using a larger variety of training data. Furthermore, we introduce novel signal-level evaluation metrics for meeting scenarios, namely the source-aggregated scale- and convolution-invariant Signal-to-Distortion Ratio (SA-SI-SDR and SA-CI-SDR), which are generalizations of the commonly used SDR-based metrics for the CSS case.
Keywords: Continuous Speech Separation; Source Separation; Graph-PIT; Dynamic Programming; Permutation Invariant Training

Schnittstelle zwischen Programmen und Forschung – Die Forschungsbegleitung InnoVET - Ertl, Hubert; Peitz, Nina-Madeleine (Datenreport zum Berufsbildungsbericht 2023. Informationen und Analysen zur Entwicklung der beruflichen Bildung)

Berufliche Fortbildung – gleichwertige Alternativen zum Hochschulabschluss. Erste Erkenntnisse aus dem Innovationswettbewerb InnoVET - Bednarz, Sigrid; Martens, Stephanie; Peitz, Nina-Madeleine (Berufsbildung in Wissenschaft und Praxis)

Class Expression Learning with Multiple Representations - Ngonga Ngomo, Axel-Cyrille; Demir, Caglar; Kouagou, N'Dah Jean; Heindorf, Stefan; Karalis, Nikoloas; Bigerl, Alexander (Compendium of Neurosymbolic Artificial Intelligence)

Spatial Diarization for Meeting Transcription with Ad-Hoc Acoustic Sensor Networks - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (Proc. Asilomar Conference on Signals, Systems, and Computers)
We propose a diarization system, that estimates “who spoke when” based on spatial information, to be used as a front-end of a meeting transcription system running on the signals gathered from an acoustic sensor network (ASN). Although the spatial distribution of the microphones is advantageous, exploiting the spatial diversity for diarization and signal enhancement is challenging, because the microphones’ positions are typically unknown, and the recorded signals are initially unsynchronized in general. Here, we approach these issues by first blindly synchronizing the signals and then estimating time differences of arrival (TDOAs). The TDOA information is exploited to estimate the speakers’ activity, even in the presence of multiple speakers being simultaneously active. This speaker activity information serves as a guide for a spatial mixture model, on which basis the individual speaker’s signals are extracted via beamforming. Finally, the extracted signals are forwarded to a speech recognizer. Additionally, a novel initialization scheme for spatial mixture models based on the TDOA estimates is proposed. Experiments conducted on real recordings from the LibriWASN data set have shown that our proposed system is advantageous compared to a system using a spatial mixture model, which does not make use of external diarization information.
Keywords: Diarization; time difference of arrival; ad-hoc acoustic sensor network; meeting transcription

Additive Manufacturing and Mechanical Properties of Auxetic and Non-Auxetic Ti24Nb4Zr8Sn Biomedical Stents: A Combined Experimental and Computational Modelling Approach - Pramanik, Sudipta; Milaege, Dennis; Hein, Maxwell; Hoyer, Kay-Peter; Schaper, Mirko (Crystals)
The effect of plaque deposition (atherosclerosis) on blood flow behaviour is investigated via computational fluid dynamics and structural mechanics simulations. To mitigate the narrowing of coronary artery atherosclerosis (stenosis), the computational modelling of auxetic and non-auxetic stents was performed in this study to minimise or even avoid these deposition agents in the future. Computational modelling was performed in unrestricted (open) conditions and restricted (in an artery) conditions. Finally, stent designs were produced by additive manufacturing, and mechanical testing of the stents was undertaken. Auxetic stent 1 and auxetic stent 2 exhibit very little foreshortening and radial recoil in unrestricted deployment conditions compared to non-auxetic stent 3. However, stent 2 shows structural instability (strut failure) during unrestricted deployment conditions. For the restricted deployment condition, stent 1 shows a higher radial recoil compared to stent 3. In the tensile test simulations, short elongation for stent 1 due to strut failure is demonstrated, whereas no structural instability is noticed for stent 2 and stent 3 until 0.5 (mm/mm) strain. The as-built samples show a significant thickening of the struts of the stents resulting in short elongations during tensile testing compared to the simulations (stent 2 and stent 3). A modelling framework for the stent deployment system that enables the selection of appropriate stent designs before in vivo testing is required. This leads to the acceleration of the development process and a reduction in time, resulting in less material wastage. The modelling framework shall be useful for doctors designing patient-specific stents.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Phase sensitivity of spatially broadband high-gain SU(1,1) interferometers - Scharwald, D.; Meier, T.; Sharapova, P. R. (Physical Review Research)
Keywords: General Physics and Astronomy

Kant and the Role(s) of Doctrines of Methods (Journal of Transcendental Philosophy)

Your Smartphone Is Watching You - Eine technikkritische Untersuchung der menschlichen Freiheit und Antiquiertheit im Zeitalter der Digitaltechnologie - Mac Award, Daria-Leona

Im Dialog: Theologische Grundlagen und religionsdidaktische Impulse für die Praxis des kokoRUs. Rezension zu Bernd Schröder/Jan Woppowa (Hg.): Theologie für den konfessionell-kooperativen Religionsunterricht. Ein Handbuch, Tübingen 2021 - Neumann, Anna (Praktische Theologie. Zeitschrift für Praxis in Kirche, Gesellschaft und Kultur)

All optical operation of a superconducting photonic interface - Thiele, Frederik; Hummel, Thomas; McCaughan, Adam N.; Brockmeier, Julian; Protte, Maximilian; Quiring, Victor; Lengeling, Sebastian; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Optics Express)
Quantum photonic processing via electro-optic components typically requires electronic links across different operation environments, especially when interfacing cryogenic components such as superconducting single photon detectors with room-temperature control and readout electronics. However, readout and driving electronics can introduce detrimental parasitic effects. Here we show an all-optical control and readout of a superconducting nanowire single photon detector (SNSPD), completely electrically decoupled from room temperature electronics. We provide the operation power for the superconducting detector via a cryogenic photodiode, and readout single photon detection signals via a cryogenic electro-optic modulator in the same cryostat. This method opens the possibility for control and readout of superconducting circuits, and feedforward for photonic quantum computing.
Keywords: Atomic and Molecular Physics; and Optics